Effectiveness of Psychosocial Intervention on Psychological Well-Being and Quality of Life Among Women with Infertility - Geetha Rajamoorthy; Theranirajan Ethiraj; Shankar Shanmugam Rajendran; Venkatesh Madhan Kumar; Anbalagan Marudan; Jayalakshmi Lakshmanan; Albeenasiril Marianathan (Journal of Pharmacy and Bioallied Sciences)
Background: Infertility is a significant medical condition characterized by the inability to conceive after one year of regular, unprotected intercourse. It has profound psychological implications, affecting overall well-being and quality of life in affected women. Psychosocial interventions have been explored as potential strategies to improve psychological well-being and life satisfaction in this population. Objective: This study aimed to assess the effectiveness of psychosocial interventions in enhancing psychological well-being and quality of life among women experiencing infertility. Methods: A quasi-experimental pretest–posttest control group design was employed. A total of 120 participants were selected using a convenient sampling method. Data were collected using a sociodemographic scale, the Ryff Psychological Well-Being Scale, and the Fertility Quality of Life (FertiQoL) questionnaire. The intervention involved structured psychosocial support sessions, and pre- and post-intervention data were analyzed using descriptive and inferential statistics. Results: The results demonstrated a significant improvement in psychological well-being and quality of life post-intervention. The mean difference in psychological well-being scores was 25.39 (P = 0.01), while the mean difference in quality of life scores was 26.45 (P = 0.001), indicating a statistically significant positive effect. Conclusion: Psychosocial interventions play a crucial role in improving the psychological well-being and quality of life of women facing infertility. These findings suggest the need for integrating psychosocial support into infertility treatment programs to enhance overall patient outcomes.